Psychotropic Polypharmacy in the US Pediatric Population: A Methodologic Critique and Commentary - Zito, Julie M.; Zhu, Yue; Safer, Daniel J. (Frontiers in Psychiatry, 2021)
Background: Psychotropic concomitant medication treatment for youth with emotional and behavioral disorders has grown significantly in the U.S. over the past 25 years. The use of pharmacy claims to analyze these trends requires the following: age of the selected population, overlapping days of use, and precision of the outcome itself. This review will also address the gaps in reporting of pediatric psychotropic polypharmacy. Methods: A PUBMED literature search was undertaken for the period 2000 through 2020 using keywords such as “pediatric” “concomitant” “polypharmacy” “multiple medications” and ‘psychotropic combinations.”; Relevant references in textbooks were also used. Only English language and U.S. studies were included, resulting in 35 studies. Results: Studies were organized into seven groups according to data sources and clinical topics: 1) population surveys; 2a) multi-state publicly insured populations; 2b) single/two state studies; 3) privately insured populations; 4) diagnosed populations; 5) foster care populations; 6) special settings. Across 20 years it is apparent that pediatric psychotropic polypharmacy affects substantially more children and adolescents today than had been the case. As many as 300,000 youth now receive 3 or more classes concomitantly. The duration of concomitant use is relatively long, e.g. 69% to 89% of annual medicated days. Finally, more adverse event reports were associated with 3-class compared with 2-class drug regimens. Discussion: Factors that contribute to the growth of pediatric psychotropic polypharmacy include: 1) predominance of the biological model in psychiatric practice; 2) invalid assumptions on efficacy of combinations, 3) limited professional awareness of metabolic and neurological adverse drug events and 4) infrequent use of appropriate deprescribing. Conclusion: A review of publications documenting pediatric psychotropic polypharmacy written over the last 20 years supports the need to standardize the methodologies used. The design of population-based studies should maximize information on the number of youth receiving regimens of 3-, 4- and 5 or more concomitant classes and the duration of such use. Next, far more post marketing research is needed to address the effectiveness, safety and tolerability of complex drug regimens prescribed for youngsters.